Real-time fully automated dosimetric computation for CT images in the clinical workflow: A feasibility study - Porzio, Massimiliano; Anam, Choirul (Frontiers in Oncology, 2022)
Background: Currently, the volume computed tomography dose index (CTDIvol), the most-used quantity to express output dose of computed tomography (CT) patient’s dose, is not related to the real sizes and attenuation properties of each patient. The size—specific dose estimates (SSDE), based on the water—equivalent diameter (DW) overcomes those issues. The proposed methods found in literature do not allow real-time computation of DW and SSDE. Purpose: To develop a software to compute DW and SSDE in a real-time clinical workflow. Method: 430 CT studies and scans of a water-filled funnel phantom were used to compute accuracy and evaluate the times required to compute the DW and SSDE. Two one-side tests (TOST) equivalence tests, Bland-Altman analysis and bootstrap-based confidence intervals estimations were used to evaluate the differences between actual diameter and DW computed automatically, and between DW computed automatically and manually. Results: The mean difference between DW computed automatically and the actual water diameter for each slice is -0.027% with TOST confidence interval equal to [-0.087%, 0.033%]. Bland-Altman bias is -0.009% [-0.016%, -0.001%] with lower limits of agreement (LoA) equal to -0.0010 [-0.094%, -0.068%] and upper LoA equal to 0.064% [0.051%, 0.077%]. The mean difference between DW computed automatically and manually is -0.014% with TOST confidence interval equal to [-0.056%, 0.028%] on phantom and 0.41% with TOST confidence interval equal to [0.358%, 0.462%] on real patients. The mean time to process a single image is 13.99 ms [13.69 ms, 14.30 ms] and the mean time to process an entire study is 11.5 s [10.62 s, 12.63 s]. Conclusion: The system shows that it is possible to have highly accurate DW and SSDE in almost real time, without affecting the clinical workflow of CT examinations.